PERANCANGAN VIDEO INFORMASI MENGENAI ASAL-USUL AIR TERJUN SEDUDO NGANJUK DENGAN TEKNIK MOTION GRAPHIC 2D - Abdul Hakam Amrulloh; abdulloh eizzi irsyada; Elfa Olivia Verdiana (Jurnal Desain Komunikasi Visual Asia, 2018)
Sedudo Waterfall is a waterfall and a tourist attraction located in Ngliman Village Sawahan, Nganjuk regency, East Java. The distance is about 30 km south of the capital Nganjuk district. Located at an altitude of 1438 meters above sea level, the height of the waterfall is about 105 meters. In an effort to present information to the public about the origin of waterfalls, it is necessary for have an Information media. Therefore motion graphic animation is one of the alternative information media that is used visual appearrance considerations of interest so that the audience can absorb the information submitted. In supporting the research process this final assigment required research methods such as data collection, analysis and concept design. The conclusion in making animation of sedudo Waterfall Nganjuk requires data and analysis with the aim that the information submitted can be received well, with the right creative concept, ranging from verbal information data that is conveyed to the design of visual ideas. From the calculation of questionnaire answers "Yes" as much as 82.8% while the answer "No" as much as 16.2%, it can be concluded based on the feasibility category of this information media very feasible to publish as information video.